State of the‐Art for Extrudate Swell of Molten Polymers: From Fundamental Understanding at Molecular Scale toward Optimal Die Design at Final Product Scale. Issue 11 (23rd August 2020) - Tang, Dahang; Marchesini, Flavio H.; Cardon, Ludwig; D'hooge, Dagmar R.
Abstract: Polymer extrudate swell is a rheological phenomenon taking place after polymer melt flow emerges the die exit of extrusion equipment, due to flow redistributions and molecular stress relaxations. The associated die design is based on the strategy of inhibiting or compensating the swelling behavior downstream the die exit. This contribution comprehensively highlights the current knowledge and plethora of experimental and modeling tools to tune extrudate swell of polymer melts. The novelty lies in the combined consideration of the impact and interplay of i) the processing parameters, ii) the die geometry, iii) the macromolecular characteristics (e.g., molar mass distribution and branching level), and iv) the additive macroscopic properties. Furthermore, the prediction of extrudate swell through various flow geometries by semiempirical expressions and fundamental viscoelastic constitutive models is compared. Specific focus is on the differential Phan–Thien–Tanner (PTT), the molecular‐based Double‐Convected POM–POM model (DCPP), and the integral Kaye–Bernstein–Kearsley–Zapas (K‐BKZ) model and their usefulness for 3D swelling descriptions, indicating the optimum model to understand the fundamental relation of molecular parameters and viscoelasticity. The relevance of such detailed analysis is also illustrated by including case studies addressing design at the final product scale. Abstract : The state of the art regarding extrudate swell of polymer melts is reviewed. The novelty of the review lies in its coverage of all important aspects, including the fundamental mechanistic understanding at the molecular scale, the combined usefulness of experimental and modeling characterization, and the control of the extrudate swell for complex geometries thus final materials.